Pelatihan Rancang Bangun Jam Sholat Otomatis Sumber Daya Solar Cell pada Pemuda Muhammadiyah Cabang Pahlawan Perjuangan dan Pulo Brayan Darat - Faisal Irsan Pasaribu; Abdul Aziz; Noorly Evalina; Cholish Cholish; Abdullah Abdulllah (ABDI SABHA (Jurnal Pengabdian kepada Masyarakat), 2021)
Through the service that will be carried out, namely by conducting training activities on the design of automatic clocks with solar panel resources using additional tools in the form of Arduino Uno, in order to be a solution amid the increasing population of unemployment in the city of Medan. Various Arduino Uno boards use different ± different types of Atmega depending on the specifications, for example the Arduino Uno uses the ATmega328 while the more sophisticated Arduino Mega 2560 uses the ATmega2560. The use of solar panel energy will be designed in the form of an LCD Prayer Timer and Adhan Alarm method with a 200WP solar cell resource using the Arduino Uno programming system. Therefore, the Muhammadiyah Youth Leaders of the Heroes of the Struggle Branch and Pulo Brayan Darat are expected to be foster partners in improving these very useful design skills, so that they can serve as examples to young people around in improving the economic level of skilled and creative organizations.